The effects of terrorism as a form of socio-political instability on tourism governance : a study of the July 2005 London Bombings - Storme, Evelien (Evelien Geertrui Andre) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2007.